(untitled) (Triyuga Academic Journal, 2025)
This study aimed to investigate teachers’ perceptions of the effectiveness of virtual classes for enhancing communication skills in English. This paper analyzed teachers’ perceptions regarding the effectiveness of virtual classes for enhancing communication skills. The result indicated that teachers react differently to virtual courses, and their reaction is based on their proficiency in using ICT tools, support of school administration, and learners’ manners during virtual teaching-learning activities. The major purpose of this study was to explore the secondary teachers’ perceptions of teaching English online. For this, I interviewed three teachers who had been taking virtual classes. The finding suggested that the teachers were quite positive towards teaching virtually despite the lack of adequate training, consistent internet services regular power supply, and suitable devices.